Histopathological findings in brain tissue obtained during epilepsy surgery - Blümcke, Ingmar; Diepgen, Thomas L. (The New England journal of medicine, 2017)
Original Article from The New England Journal of Medicine - Histopathological Findings in Brain Tissue Obtained during Epilepsy Surgery